Dangerous Decisions - Mumford, E. author. aut Link
XI, 233 p.
Keywords: In a world where technology is continually advancing, and problems are becoming more and more complex, established practices for decision making and problem solving are no longer effective. In this new book, however, Enid Mumford draws on her wealth of experience in management, business schools, and working with the police and other professional problem solvers to show us how to tackle complex problems efficiently. With drugs and cyber-crime as her main examples Professor Mumford shows how these topical, yet apparently permanent problems, could be approached. She does this by looking at how the criminals themselves have overcome legal obstacles, and other problems to make the drug trafficking industry the second largest in the world today, and the relative newcomer, electronic fraud, a multi-billion dollar problem already. These crimes, which in themselves lead to more crime from petty theft to support a drug habit, to international money laundering, are incredibly complex, and yet the book shows us that there is not only a way forward with these issues, but a way to approach all complex problems with efficiency and competency, wherever they occur in our lives.